2018
DOI: 10.1093/infdis/jiy306
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Torque Teno Virus Viremia as a Prospective Biomarker for Infectious Disease in Kidney Allograft Recipients

Abstract: TTV quantification predicts infection after kidney transplantation and might be a potential tool to tailor immunosuppressive drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
142
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(164 citation statements)
references
References 25 publications
17
142
3
2
Order By: Relevance
“…In addition, we did not find any association between recipient CMV serology and pretransplant TTV DNA, in contrast with a previous report involving healthy individuals . After transplant, patients with negative serology (who presented a higher incidence of CMV infection) had a higher TTV DNA load, which was consistent with previous findings . Although a potential association with CMV primoinfection after transplant has previously been hypothesized, our results showed that this difference was only significant in those patients who received triple IS, the same group that also presented a higher incidence of CMV infection.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In addition, we did not find any association between recipient CMV serology and pretransplant TTV DNA, in contrast with a previous report involving healthy individuals . After transplant, patients with negative serology (who presented a higher incidence of CMV infection) had a higher TTV DNA load, which was consistent with previous findings . Although a potential association with CMV primoinfection after transplant has previously been hypothesized, our results showed that this difference was only significant in those patients who received triple IS, the same group that also presented a higher incidence of CMV infection.…”
Section: Discussionsupporting
confidence: 77%
“…(18) In addition, Strassl et al recently showed that an MMF dose 1.5 g or higher was the only IS therapy associated with a higher TTV viremia in kidney transplant recipients. (19) In contrast, in our cohort, patients with triple therapy did not present fewer episodes of rejection as might have been expected in light of the higher state of IS suggested. Nevertheless, immune mechanisms that lead to graft rejection are different than those that protect a host from infections and thus these 2 complications are not mutually exclusive.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…28 The number of epitopes was significantly higher even after subtracting CMV epitopes, which echoes findings of several recently published studies in which torque-teno virus (a ubiquitous virus thought to be nonpathogenic, but serves as a marker of overall immunosuppression) and herpesvirus reactivation predicted reactivation of other viruses. 29,30 It may be that persons who reactivated CMV were also more likely to subclinically reactivate other viruses due to overall immunosuppression, leading to the observed expansion of non-CMV viral epitopes. Heterogeneity in CMV epitope recognition could potentially help explain why CMV-positive donors may not be able to adequately control reactivation of a recipient's specific CMV strain.…”
Section: Non-cmv Epitopesmentioning
confidence: 99%